Air Consumption of Pneumatic Servo Table System - Miyajima, Takashi; Kawashima, Kenji; Fujita, Toshinori; Sakaki, Kazutoshi; Kagawa, Toshiharu (Systems Modeling and Simulation: Theory and Applications, 2005)
We have developed a pneumatic servo table system, which is a precise positioning system using air power. In this paper, the energy consumption of the pneumatic servo table system is investigated. To clarify the energy consumption, the air consumption must be clarified. We analyzed the air consumption of the system and became clear theoretically that the air consumption could be separated to the consumption to move the table and that to accelerate. The certainty of the analysis is confirmed with the experimental result using quick response laminar flow meter. Furthermore the best reference trajectory is derived on the point of energy saving.